Caring for the Animal Caregiver—Occupational Health, Human-Animal Bond and Compassion Fatigue - Van Hooser, J. Preston; Pekow, Cynthia; Nguyen, Holly M.; D'Urso, Dominic M.; Kerner, Sara E.; Thompson-Iritani, Sally (Frontiers in Veterinary Science, 2021)
Laboratory Animal Professionals experience many positive and rewarding interactions when caring for and working with research animals. However, these professionals also may experience conflicting feelings and exhaustion when the work is stressful due to factors such as limited resources, making end of life decisions, dealing with conflicting priorities, and negotiating animal care priorities with colleagues. These stresses may be further complicated by each individual’s self-understanding and emotional investment in the human-animal bond. The term used for this type of complex emotional conflict and exhaustion is Compassion Fatigue. Compassion Fatigue in the Laboratory Animal Science setting is a combination of physical, emotional and psychological depletion associated with working with and caring for animals and their well-being in a research environment. The University of Washington has developed a Compassion in Science Program called Dare2Care which emphasizes self-care and helps Laboratory Animal Professionals identify stress factors and work toward a personal solution to relieve stress. The first step in developing a resiliency program is to assess the current culture and needs of the organization. At an institutional level we identified that we needed increased communication concerning study endpoints, as well as identified individuals with whom affected personnel can talk about personal concerns. We also implemented community events to reflect on the positive aspects of this field of work. We improved the physical work environment, and provided outlets established for personnel to express feelings via written word or artistically. Lastly, we worked to revise our occupational health screening form to include additional health or workplace concerns (e.g., Compassion Fatigue) not covered by the questionnaire, and added a component of Compassion Fatigue awareness in our training program. Here we review the importance of identifying Compassion Fatigue in the animal research setting, focus on developing a compassion resiliency culture and provide tools and coping strategies to validate and strengthen the human-research animal bond and to sustain the care that is necessary for both people and research animals.